Gold(III) Alkyne Complexes: Bonding and Reaction Pathways. Issue 44 (2nd October 2017) - Rocchigiani, Luca; Fernandez‐Cestau, Julio; Agonigi, Gabriele; Chambrier, Isabelle; Budzelaar, Peter H. M.; Bochmann, Manfred
Abstract: The synthesis and characterization of hitherto hypothetical Au III π‐alkyne complexes is reported. Bonding and stability depend strongly on the trans effect and steric factors. Bonding characteristics shed light on the reasons for the very different stabilities between the classical alkyne complexes of Pt II and their drastically more reactive Au III congeners. Lack of back‐bonding facilitates alkyne slippage, which is energetically less costly for gold than for platinum and explains the propensity of gold to facilitate C−C bond formation. Cycloaddition followed by aryl migration and reductive deprotonation is presented as a new reaction sequence in gold chemistry. Abstract : Good as gold : The synthesis of hitherto hypothetical gold(III) π‐alkyne complexes highlights the differences between classical platinum alkyne complexes and their drastically more reactive Au III congeners. Alkyne bonding in these complexes is subject to a strong trans influence, with ligands trans to a pyridine N atom being bound significantly more strongly than those trans to an anionic C donor.